2007
DOI: 10.1002/cjoc.200790091
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Photocatalytic Properties of Ti1−xZrxO2 Solid Solution

Abstract: A series of Ti 1-x Zr x O 2 materials were synthesized through a multistep sol-gel process. The structural characteristics were investigated using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and Raman measurements. The experimental results showed that a solid solution could be obtained at low Zr/(Ti+Zr) molar ratios (x ≤0.319). Raman measurements exhibited that the presence of zirconium in the solid solutions greatly retarded the amorphous-anatase and anatase-rutile transitions. The diffuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…In general, one could expect the band gap variation in this binary oxide from well known 3.2 eV of anatase TiO 2 to 5.1 eV of ZrO 2 . This tendency has been confirmed in previous studies of these mixed oxide solids . Our spectral measurements presented in Figure showed no significant variation of the band gap energy of Zr x Ti 1‐x O 2 with the increase of x from 0 to 0.3, while a stronger increase of E g appeared at a higher Zr content x>0.4.…”
Section: Resultssupporting
confidence: 88%
“…In general, one could expect the band gap variation in this binary oxide from well known 3.2 eV of anatase TiO 2 to 5.1 eV of ZrO 2 . This tendency has been confirmed in previous studies of these mixed oxide solids . Our spectral measurements presented in Figure showed no significant variation of the band gap energy of Zr x Ti 1‐x O 2 with the increase of x from 0 to 0.3, while a stronger increase of E g appeared at a higher Zr content x>0.4.…”
Section: Resultssupporting
confidence: 88%
“…The value of ΔΑ is independent on the influence of the absorption and light scatting of cobalt-iron PBAs when the absorbance due to the absorption and scattering of PBAs at each of the three wavelengths is linear with the wavelength. [17][18][19][20][21][22] Thus proper choices of the setting absorption wavelengths are crucial, which are required to ensure that the absorbance of cobalt-iron PBAs due to the absorption and scattering in the wavelength range between λ 1 and λ 3 is linear with the wavelength and the values of ΔΑ for K 3 Fe(CN) 6 are sufficiently large. The values of λ 1 and λ 3 were carefully selected to be 410 nm and 440 nm respectively in our study.…”
Section: Three Wavelength Spectrophotometry Measurementsmentioning
confidence: 99%
“…Chow et al [5] reported spherical cobalt-iron PBAs nanoparticles in water-in-oil (w/o) microemulsions containing nonionic surfactants. Vaucher et al [6] obtained cobalt hexacyanoferrate nanoparticles which are well-defined and uniform in size within the range of (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) nm in microemulsion containing anionic surfactant sodium bis(2-ethylhexy) sulfosuccinate (aerosol OT or AOT). Zhao and co-worker synthesized nanoscale cobalt-iron PBAs with shapes of hollow, cube, and sphere in w/o microemulsions containing nonionic surfactant polyoxyethylen tertocthlphenyl ether (Triton X-100) and cationic surfactant cetyltrimethyl ammonium bromide (CTAB).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is well known that the photocatalytic activity of transition metal ion doped TiO 2 had a complex relationship with the dopant concentration, the d electronic configuration, the distribution of dopant, etc. [19][20][21][22]. Undoubtedly, the photocatalytic mechanism of co-doped samples would be more complicated and desire of further exploration.…”
Section: Introductionmentioning
confidence: 97%